Posibles casos de metátesis en la lengua de las inscripciones jeroglíficas mayas - Baboshkin, Maxim (El Colegio de México, A.C., 2022)
The aim of this paper is to provide arguments in favor of the presence of the phonological process of metathesis in the language of Mayan hieroglyphic inscriptions, based on the comparative data. The main patterns of the reordering of segments, found thus far in the Lowland Mayan languages, are examined. The modern and colonial cases are compared with those from the hieroglyphic texts, with a special focus on the transposition in the CV-CVC structures. Primary traits of this phenomenon are described, and the possibility of the influence of the scribal practice on the development of some metathetic forms is hypothesized.